Analisis NAPS, ROE dan EPS Sebagai Dasar Pengambilan Keputusan Investasi Perusahaan property and real estate - Sri Yati (JURNAL INTEGRASI, 2012)
This research aims to determine the performance of the stock of property and real estate property companies listed on the Indonesia Stock Exchange by using analysis of NAPS, ROE and EPS as a basis for decision making for equity investments. The sample was two property and real estate companies listed consistently in the Indonesia Stock Exchange for the period 2006-2008, PT. Jaya Real Property, Tbk. and PT. Suryamas Dutamakmur, Tbk. Analytical techniques used in this study was NAPS (Net Asset Per Share), ROE (Return on Equity) and EPS (Earning Per Share). The results of the analysis of NAPS, ROE and EPS in each company, in 2008, the first good investment should be done at PT. Jaya Real Property, Tbk as the performance of the company showed a tendency to hold up steadily. Then, investments can be made in PT. Suryamas Dutamakmur, Tbk. Factors to consider in the application of equity investment in Indonesia is the condition of the market, which is the market price is determined by the strength of demand or supply and changes in the company of potential risks.